Hubungan Antara Komitmen Organisasi Dan Person-Organization Fit Dengan Intensi Turnover Pada Karyawan Kontrak Pt. X Di Tegal - Chalifah Chairunnisa; Tanti Susilarini (Universitas Persada Indonesia YAI, 2022)
This study aims to knowing the relationship between organizational commitment and personorganizationfit with turnover intention in contract employees of PT. X in Tegal. The sample in thisstudy amounted to 132 subjects with data collection method using convenience sampling technique.The tools are used the turnover intention scale (24 items,  = 0.917), the organizational commitmentscale (20 items, = 0.901) and the person- organization fit scale (28 items,  = 0.932). Based on theresults of the study, there is a negative relationship between organizational commitment and personorganizationfit with turnover intention.